How Do Leaf-Cutting Ants Recognize Antagonistic Microbes in Their Fungal Crops? - Goes, Aryel C.; Barcoto, Mariana O.; Kooij, Pepijn W.; Bueno, Odair C.; Rodrigues, Andre (Frontiers in Ecology and Evolution, 2020)
Leaf-cutting ants employ diverse behavioral strategies for promoting the growth of fungal cultivars in a structure known as fungus-garden. As a nutritionally-rich resource for the ants, the fungal crop is threatened by microbial antagonists and pathogens. Strategies for protecting the garden against harmful microbes have been described in detail, though the process of microbial threat recognition is not fully understood. Here, we review the literature on leaf-cutting ants’ social immunity traits, in search of possibilities by which workers recognize harmful microbes in their system. Based on current data, we suggest mechanisms regarding (1) chemical recognition, where discrimination could be related to chemical cues from the antagonistic microbe or semiochemicals released by the fungus-garden during harmful interactions, or (2) through associative learning when workers would connect the microbe cues with a damage in the fungus-garden, developing a “colony-level memory” towards this threat. We also discuss evidence supporting ant-fungus communication as key for maintaining the health of the fungus-garden, as well as experimental setups for future evaluation of threat detection and recognition by leaf-cutter ants.